Daylighting and readers’ satisfaction: Raja Tun Uda Public Library, Shah Alam / Ahmad Ridzwan Othman and Maz Aiera Mohd Mazli. - Othman, Ahmad Ridzwan; Mohd Mazli, Maz Aiera (Universiti Teknologi MARA Cawangan Selangor, 2018)
Designing library study environment is important to the mood, motivation and performance of individual because interior design plays an important role on human mood and social behaviours. Lighting, as a control architectural tool, gives important influences on users’ perception behaviour and visual comfort in libraries. A public library in Shah Alam was chosen as the main subject. The result found that the library users prefer the seat near daylighted area, but the time spend in the library is not really affected by daylighting. Besides for visual comfort, daylighting is not the only contributor to overall comfort and user’s satisfaction.